Evaluating MBA Graduates Holistic Leadership Competencies Case Study (MBA SBM ITB and MBA ITB Graduates Who Work In PT. Telkom Indonesia) - Karnova, Sarach; Welly, John (The Indonesian Journal of Business Administration, 2017)
Abstract- MBA school’ challenge on producing competent leaders is being debated for a long time. Several transformations in MBA school has been done in order meet business and society’ need of leaders. These stakeholders need leaders who are not only thinking of profit, but also able to run business ethically, contribute betterment for company, human society and environment.  There are lots of leadership model has been produced. Quatro, Waldman, Galvin (2007) proposed leadership model which offer holistic approach of leadership competencies. These skills are mapped into 4 domains of leadership that consist of analytical, conceptual, emotional and spiritual (ACES). Based on this model, an effective leader should practice competencies from all 4 leadership domains. This research aimed to evaluate MBA ITB graduates who is working in PT Telkom Indonesia in terms of the implementation of holistic leadership competencies mapped by ACES model. The results of this evaluation are used as input for improving the quality of teaching methods in MBA ITB. The supported data is obtained through questionnaire were spread to MBA ITB graduates in PT Telkom Indonesia and interview with some lecturers MBA ITB.  From the findings, the most important skills of a leader come from Spiritual and Emotional domains. 2 remaining domains also resulted high value, thus still need to be developed. Some possible improvement that author offer to provide cross-disciplinary courses, building partnership with company, assigning real project to students, re-working case study, also improving lecturing and lecturers.  By implementing these improvements, author believe MBA ITB will have better performance and produce better leaders for business and societyKeywords: Leadership, human resource, MBA School